2019
DOI: 10.1016/j.neo.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Iroquois Homeobox 1 Acts as a True Tumor Suppressor in Multiple Organs by Regulating Cell Cycle Progression

Abstract: Iroquois homeobox 1 (IRX1) belongs to the Iroquois homeobox family known to play an important role during embryonic development. Interestingly, however, recent studies have suggested that IRX1 also acts as a tumor suppressor. Here, we use homozygous knockout mutants of zebrafish to demonstrate that the IRX1 gene is a true tumor suppressor gene and mechanism of the tumor suppression is mediated by repressing cell cycle progression. In this study, we found that knockout of zebrafish Irx1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Homeobox domains are characteristic protein folds that bind DNA and regulate the expression of target genes during development and differentiation. Jung et al analyzed the function of IRX1 in the development of zebrafish and they demonstrated that IRX1 acts a tumor suppressor in multiple organs by regulating the cell cycle progression [20]. Here, we revealed by GSEA that IRX1 expression is negatively correlated with E2F-and Myc-targets in several lung cancer data sets (Table 1).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Homeobox domains are characteristic protein folds that bind DNA and regulate the expression of target genes during development and differentiation. Jung et al analyzed the function of IRX1 in the development of zebrafish and they demonstrated that IRX1 acts a tumor suppressor in multiple organs by regulating the cell cycle progression [20]. Here, we revealed by GSEA that IRX1 expression is negatively correlated with E2F-and Myc-targets in several lung cancer data sets (Table 1).…”
Section: Discussionmentioning
confidence: 65%
“…The promoter region of IRX1 is located in a CpG island ( Figure 1b) and hypermethylation of IRX1 has been found in gastric cancer [15], head and neck squamous carcinoma [16], and other cancer entities [17][18][19]. Functional data indicate that IRX1 acts as an epigenetically regulated tumor suppressor in different types of cancer [15,20].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a recent implementation, the CRISPR/Cas9 system has been already applied to the zebrafish cancer research field [82][83][84][85][86][87][88][89][90] (Table 4). Iroquois homeobox 1 (IRX1) is an homeobox-containing transcription factor playing a role in embryonic development and suspected to act as a tumor suppressor gene in head and neck squamous cell carcinoma, gastric cancers and glioma [106][107][108][109].…”
Section: Clustered Regularly Interspaced Short Palindromic Repeats Rnmentioning
confidence: 99%
“…In zebrafish, Irx1 is encoded by two ohnologues irx1a and irx1b. The group of Seung Woo Park (Yonsei University College of Medicine, Seoul, Korea) used the TALEN technology to inactivate irx1a, while irx1b mutants were generated using the CRISPR/Cas9 system [82]. Homozygous mutants for both irx1a and irx1b (irx1a -/-; irx1b -/-) are malformed and die within 6 months of age.…”
Section: Clustered Regularly Interspaced Short Palindromic Repeats Rnmentioning
confidence: 99%
See 1 more Smart Citation